Comparing vision and macular thickness in neovascular age-related macular degeneration, diabetic macular oedema and retinal vein occlusion patients treated with intravitreal antivascular endothelial growth factor injections in clinical practice - Alex W Hewitt; Rajya L Gurung; Liesel M FitzGerald; Bennet J McComish; Nitin Verma; Kathryn P Burdon (BMJ Open Ophthalmology, 2021)
Objective To compare the visual outcomes of intravitreal antivascular endothelial growth factor (anti-VEGF) injections in neovascular age-related macular degeneration (nAMD), diabetic macular oedema (DMO) and retinal vein occlusion (RVO) in a real-world setting.Methods and analysis Retrospective analysis of data from the Tasmanian Ophthalmic Biobank database. The median change in best-corrected visual acuity (BCVA) between baseline and 12 months post initiating intravitreal anti-VEGF treatment were compared between the three diseases. Final BCVA, central macular thickness (CMT), cumulative number of injections and overall predictors of change in BCVA and CMT were also determined.Results At 12 months, change in BCVA was significantly different between nAMD, DMO and RVO cohorts (p=0.032), with lower median change for DMO (2 letters, range −5 to 20) than for RVO (11 letters, range −20 to 35). Likewise, CMT change was significantly different between the three cohorts (p=0.022), with a smaller reduction in CMT in DMO (−54 µm, range −482 to 50) than RVO patients (−137 µm, range −478 to 43; p=0.033). Total number of injections received (p=0.028) and final BCVA score (p=0.024) were also significantly different between the groups. Baseline BCVA was a negative predictor (p=0.042) and baseline CMT a positive predictor (p<0.001) of outcome. After adjusting for baseline BCVA and CMT, diagnosis of nAMD or RVO was a predictor of visual improvement compared with the DMO.Conclusions At the end of 12 months, nAMD and RVO cohorts had the greatest improvement in BCVA, however the final BCVA for DMO was significantly better than for nAMD.